Skrining Depresi Post Patrum Pada Ibu Pasca Melahirkan di Wilayah Kerja Puskesmas Cancar Kabupaten Manggarai - Nur Dafiq; Silfia Angela Norce Halu; Fransiska Nova Nanur; Maria Sriana Banul (Universitas Malahayati, 2026)
ABSTRACT The pregnancy period to the moment of birth is a complex event that affects a mother. Postpartum depression is a mood disorder that occurs during the postpartum period and can have a significant impact on the mother and baby and the family environment. The purpose of this study is to screen for postpartum depression in postpartum mothers in the working area of the Cancar health center. The research method used is quantitative description, where the population is postpartum mothers and the sample is postpartum mothers in the Cancar health center area. The results of postpartum depression screening using the EPDS questionnaire were mostly seventh-day postpartum mothers experiencing postpartum depression. This is proven that as many as 57.57% of seventh-day postpartum mothers have an EPDS score of ≥10, meaning they have postpartum depression and 42.42% do not experience postpartum depression. Young people ( 35 years old) have a risk of experiencing postpartum depression, which is as many as 52 people (53.2%). that mothers who do not work as many as 22 people (64.7%) have a risk of postpartum depression. Educational characteristics, mothers who experience postpartum depression the most at the high school level are (27.27%). Keywords: Screening, Postpartum Mother, Postpartum Depression. ABSTRAK Masa kehamilan hingga saat melahiran merupakan suatu peristiwa kompleks yang berpengaruh bagi seorang ibu. Depresi pascapersalinan merupakan gangguan suasana hati yang terjadi pada masa nifas dan dapat menimbulkan dampak signifikan bagi ibu dan bayi dan lingkunga keluarga. Tujuan penelitian ini adalah skrining depresi postpartum pada ibu pasca melahirkan di wilayah kerja puskesmas Cancar. Metode penelitian yang digunakan yaitu kuantitatif deskripsi, dimana populasi yaitu ibu pasca nifas dan sampel yaitu ibu nifas yang berada di wilayah puskesmas Cancar. Hasil skrining depresi postpartum menggunakan kuisioner EPDS sebagian besar ibu postpartum hari ketujuh mengalami depresi postpartum. Hal ini dibuktikan bahwa sebanyak 57,57% ibu postpartum hari ketujuh memiliki skor EPDS ≥10 artinya mengalami depresi postpartum dan 42,42% tidak mengalami depresi postpartum. usia muda ( 35 tahun) memiliki resiko untuk mengalami depresi postpartum, yaitu sebanyak 52 orang (53.2 %). bahwa ibu tidak bekerja sebanyak 22 orang (64,7%) memiliki resiko depresi postpartum. karakteristik pendidikan, ibu yang mengalami depresi postpartum paling banyak pada jenjang SMA yaitu sebanyak (27,27%). Kata Kunci: Skrining, Ibu Nifas, Depresi Postpartum.